2020
DOI: 10.1002/cam4.3241
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index trajectories and prostate cancer risk: Results from the EPICAP study

Abstract: Elevated body mass index (BMI) has been inconsistently associated with prostate cancer occurrence but it has been suggested that life course adulthood obesity may be associated with an increased risk of prostate cancer. However, few studies have investigated lifetime BMI and prostate cancer risk. We analyzed life course BMI trajectories on prostate cancer risk based on data from the Epidemiological study of Prostate Cancer (EPICAP). We included in our analyses 781 incident prostate cancer cases and 829 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…As expected, aging was the most potent factor in our model. Higher BMI was associated with increased risk of PC, which is consistent with a previous Korean prediction model [15] and other epidemiological studies [46,47]. As found in previous studies, persons with hypertension showed a higher risk of PC [28], and DM was inversely associated with PC incidence [26,27].…”
Section: Predictor Variables For Pc Risksupporting
confidence: 90%
“…As expected, aging was the most potent factor in our model. Higher BMI was associated with increased risk of PC, which is consistent with a previous Korean prediction model [15] and other epidemiological studies [46,47]. As found in previous studies, persons with hypertension showed a higher risk of PC [28], and DM was inversely associated with PC incidence [26,27].…”
Section: Predictor Variables For Pc Risksupporting
confidence: 90%
“…Of the 47 studies that included both males and females, 18 studies reported trajectories only stratified by sex. The most common study design used was a cohort study ( n = 55), three studies were case‐control designs 27,30,35 with measures of recalled body size from different age periods and one study was a randomized control trial 25 . Table in the Appendix outlines more detailed characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 22 studies with growth trajectories beginning in childhood, five studies 20,22,38,41,51 had measures until young adulthood (19–23 years old), 12 studies 16,30–32,36,42–50 had measures until midadulthood (38–50 years old), and five studies 5,14,17,18,46 had measures until older adulthood (60–80 years old). The remaining studies ( n = 37) 15,19,21–29,33–35,37,39,40,52–72 did not include any childhood measures, and only included measures >18 years of age. Of these 37 studies that only reported growth measures in adulthood, six studies 26,61–64,70 only included measures during the older adulthood period of life (≥60 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we performed subsequent analyses to explore the potential mediatory role of BMI, Lp(a) and testosterone in the associations between drug targets and prostate cancer risk. Elevated BMI has been found to associated with increased prostate cancer risk in multiple observational studies [24][25][26], whereas MR study identified evidence for an inversed association between them [66]. In addition, levels of testosterone were found to be strongly correlated with the risk of prostate cancer in both observational [28] and MR [29] studies.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of LDL-c lowering drugs, LDLR expression and circulating LDL-c on advanced prostate cancer and early-onset prostate cancer was also investigated. Finally, we evaluated the genetically proxied effects of LDL-c lowering drugs on several traits previously implicated to play a role in prostate cancer risk (body mass index (BMI) [24][25][26], lipoprotein A (Lp(a)) [27] and testosterone [28,29]) to discern whether they may reside along the pathways between therapeutic targets and risk of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%